From Theodulf to Rashi and beyond texts, techniques, and transfer in western European exegesis (800-1100) - Heil, Johannes 1961-; Shimahara, Sumi 1973- (Brill, 2022)
"This book offers a new and inclusive approach to Western exegesis up to 1100. For too long, modern scholars have examined Jewish and Christian exegesis apart from each other. This is not surprising, given how religious, social, and linguistic borders separated Jews and Christians. But they worked to a great extent on the same texts. Christians were keenly aware that they relied on translation. The contributions to this volume reveal how both sides worked on parallel tracks, posing similar questions and employing more or less the same techniques, and in some rare instances, interdependently"
Includes bibliographical references and index
Keywords: Geschichte 800-1100; Exegese; Westeuropa; Bible / Criticism, interpretation, etc / History / Middle Ages, 600-1500; Christianity and other religions / Judaisum; Judaism / Relations / Christianity; Aufsatzsammlung